Новые данные рентгенометрического исследования ископаемых костей наземных позвоночных - Бачинский, Г.А.; Мельников, В.С. (Вестник зоологии, 1967)
X-ray investigation of samples of fossil bones from different Neogene and Anthropogene deposits in the Ukraine shows that basic mineral of fresh and fossil bones is represented by carbonateapatite like to francolite, extent of decrystallization being increased regularly with increase of the geological age of bones. Some changes in the content of components in anionic skeleton take place with increasing the geological age of bones from the present to miocene, as shown by decreasing the interplanar spacings. These conclusions give the prospects for subsequent development of new (X-ray) method for determination of geological age of fossil bones, by which even more ancient than latepliocenic remains of vertebrates can be analysed.